Relationship between intangible assets, called-out directors’ operational dichotomy and corporate financial performance - Asien, Etumudon Ndidi (Goodwood Publishing, 2023)
Purpose: This study examines the relationship between intangible assets (INTAN), Executive Directors (EDs), Non-Executive Directors (NEDs) and corporate financial performance. Research methodology: This study utilizes multivariate regression models to analyze datasets of 670 firm-year observations, from 2012-2020. Results: Our main OLS and FE multivariate regression results in Model 2 suggest that INTAN, CHAIR, CEOs, CFOs and strong BDIND significantly increase corporate financial performance. In Model 1 of our main tables (Tables 5 and 6), INTAN and CHAIR do not appear to be significant, although their observed signs suggest that they increase corporate financial performance. Except for YEAR, the rest control variables significantly affect corporate financial performance. Taken together, these results provide conclusive evidence that INTAN, CHAIR, CEOs, CFOs and BDIND have positive and significant effects on corporate financial performance. We, therefore, recommend that Nigerian companies should strengthen their corporate governance mechanisms to boost financial performance. Limitation: The study is limited by incomplete data on all variables, especially relating to running Fixed Effects models, where the data is unbalanced. Contribution: The study extends the literature on call-out Board members’ operational dichotomy. Novelty: This is the first from a developing economy to make a testable hypothesis on the relationship between intangible assets and corporate financial performance.